Value co-creation through digital service capabilities: the role of human factors. Issue 3 (3rd June 2019) - Saunila, Minna; Ukko, Juhani; Rantala, Tero
Abstract : Purpose: The purpose of this paper is to explore the different human factor characteristics that are emphasized when co-creating value through digital service capabilities. Design/methodology/approach: Empirical data are gathered from two small companies that deliver digital services and products in business-to-business markets. Findings: The study highlights the role and importance of human factors as reflected in employees' customer orientation while delivering digital service capabilities. The role of human factors also changes during the digital service production process. Originality/value: Developing digital service capability is positively associated with value co-creation, but it requires new skills: firms need to evaluate their mechanisms for supporting continuous learning about the properties of digital technologies. To the authors' knowledge, this is the first study to focus on the role of human factors in in developing digital service capabilities.